The Social Media Manifesto - Hallam, Jed.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
The Social Media Manifesto is a handbook to enable leaders across the business to understand how social technology can be incorporated into their company. Including case studies from Google, IBM, Spotify, Unilever, and Coca-Cola, it provides insight and practical advice for managers to implement their own social business plans.
Keywords: Marketing; Leadership; International business enterprises; Management; Industrial management; Public relations; E-business.; Electronic commerce; E-commerce.; Marketing; Business Strategy/Leadership.; International Business; Innovation/Technology Management; Corporate Communication/Public Relations; e-Business/e-Commerce.